Aspects of endocrine disruptors remediation using in vitro and in vivo ecotoxicological assays - Silva, Juliana Polloni [UNESP] (2017)
Chemicals with potential to cause endocrine disruption in vertebrates and invertebrates have been detected at low concentrations in the world's aquatic environments. Therefore, the search for removal methodologies in aquatic environments became a worldwide interest. The aim of this research was to investigate three materials (powered activated carbon - PAC, powered natural zeolites - ZP and aquatic humic substances - AHS) in chemical and ecotoxicological remediation of 17ß-estradiol (E2) and 17α-ethinylestradiol (EE2) in water through chemical and biological tests in vitro and in vivo. An environmentally relevant concentration of hormones (30 ng.L-1) was used during laboratory tests. The results obtained through an extensive list of morphological, reproductive and histological parameters showed the significant impact of HSFs on the development and maintenance of exposed fish. The superior efficiency of PAC was verified in relation to the other substrates in the endocrine disrupting chemicals (EDCs) removal in water. Nevertheless, their properties did not guarantee the same performance to the environmental samples, neither allow biological injuries monitored to be recovered after the period of depuration investigated. An additional study also allowed the development of a histochemical protocol capable of identifying the production of vitellogenin (VTG) prompted by exposure to the synthetic steroid EE2.